Implementasi Kebijakan Pemberian Santunan Terhadap Korban Kecelakaan Lalu Lintas Jalan di PT Jasa Raharja Sukabumi - Vivit Fitria Hidayati; Tuah Nur; Dian Purwanti (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
This study is based on the phenomenon of the problem that the researcher found in the field regarding the implementation of the policy of providing compensation to victims of traffic accidents by PT Jasa Raharja Sukabumi. The phenomena of this research problem are: 1) Limited number of employees resulting in multiple positions; 2) Lack of socialization so that there are still many people who are confused about managing accident compensation claims; and 3) The online compensation claim process has not been optimal yet. This study aims to determine the implementation of the policy of providing work accident compensation at PT Jasa Raharja Sukabumi. The research method used is a descriptive method with a qualitative approach. The determination of informants in this study uses snowball sampling technique. Whereas, the data collection techniques which were used by researchers are observation, interviews, and documentation. This study uses the theory of policy implementation according to Jones (1996). The results of this study indicate that the implementation of the policy of providing accident compensation by Jasa Raharja Sukabumi has run quite well in terms of organization and implementation. However, socialization is still less optimal, as can be seen from the lack of information regarding the procedure for claiming accident compensation received by most people.